Hitherto Unreported Pattern of Complex Obstructive Partial Anomalous Pulmonary Venous Drainage with Dual Drainage of Accessory Pulmonary Veins - Garg, Dollphy; Sharma, Arun; Naganur, Sanjeev Hanumantacharya; Singhal, Manphool (Indian Journal of Radiology and Imaging, 2023)
Partial anomalous pulmonary venous drainage is a congenital cardiac disorder characterized by abnormal drainage of one or more pulmonary veins into the systemic circulation. It can be isolated or associated with other congenital cardiac anomalies, most commonly atrial septal defect and patent ductus arteriosus. The clinical presentation is variable and depends on the degree of shunting and associated cardiac anomalies. Many patients usually remain asymptomatic until late in life. In this article, we presented a complex case of obstructive partial anomalous pulmonary venous drainage with dual drainage of bilateral accessory pulmonary veins with intact interatrial septum in conjunction with a patent ductus arteriosus and a ventricular septal defect. This pattern is incredibly rare and to the best of our knowledge has not been previously reported. Computed tomography played a pivotal role in precisely elucidating the intricate anatomy in this case with a complex pattern of anomalous pulmonary venous drainage.
Keywords: accessory pulmonary veins; PAPVC; dual drainage; obstructive partial anomalous pulmonary venous drainage; partial anomalous pulmonary venous drainage